2009
DOI: 10.1039/b810802a
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium polyoxoanion-bridged macrocyclic metal complexes: from one-dimensional to three-dimensional structures

Abstract: The reactions of four-coordinated transition metal macrocyclic complexes [ML](ClO(4))(2) (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane, M = Ni, Cu) with NH4VO3 under different conditions gave four coordination polymers of {[(CuL)(0.5)(H2L)(1.5)][H2V10O2)] x 6H(2)O}(n) (1x6H(2)O), {[NiL](3)[V16O38(H2O)] x 6H(2)O}(n) (2 x 6H(2)O), {[NiL][VO(3)](2) x 0.33H2O}(n) (3.0.33H(2)O), and {[CuL][VO(3)](2) x 0.33H(2)O}(n) (4 x 0.33H2O). Single crystal X-ray diffraction analyses reveal that four diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…As [NiL] 2+ in these polymers assumes only one coordination mode, the diverse structures of these coordination polymers originate from the structural diversity of the vanadium polyoxoanions, which are closely related to the pH of the reaction solution. To the best of our knowledge, the [V 16 O 42 ] n 4 n – sheet in 1 , [V 6 O 18 ] 6– ring in 2 , [VO 3 ] n n – chain in 3 , and [VO 3 ] n n – sheet in 4 have already been reported in the literature, , whereas the [V 10 O 29 ] n 8 n – chain in 5 is reported for the first time in this work . The results of this work reveal that vanadium polyoxoanions really can show diverse structures under slightly different synthetic conditions.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…As [NiL] 2+ in these polymers assumes only one coordination mode, the diverse structures of these coordination polymers originate from the structural diversity of the vanadium polyoxoanions, which are closely related to the pH of the reaction solution. To the best of our knowledge, the [V 16 O 42 ] n 4 n – sheet in 1 , [V 6 O 18 ] 6– ring in 2 , [VO 3 ] n n – chain in 3 , and [VO 3 ] n n – sheet in 4 have already been reported in the literature, , whereas the [V 10 O 29 ] n 8 n – chain in 5 is reported for the first time in this work . The results of this work reveal that vanadium polyoxoanions really can show diverse structures under slightly different synthetic conditions.…”
Section: Resultsmentioning
confidence: 58%
“…A number of inorganic–organic hybrids with 1D, 2D, and 3D extended structures have been obtained by using transition‐metal complexes and polyoxovanadate clusters as building blocks . We have also constructed several inorganic–organic hybrids by using the transition‐metal macrocyclic complex [ML 0 ] 2+ (L 0 = 5,5,7,12,12,14‐hexamethyl‐1,4,8,11‐tetraazacyclotetradecane) and polyoxometalates . We found that the transition‐metal macrocyclic complexes [ML 0 ] 2+ are good building blocks for the construction of hybrid materials, as four of the six coordination sites of the metal ion are occupied by the ligand and the other two coordination sites in trans positions are vacant, which directs the orientation of the growth of the structural unit during the assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…The protonation state of the decavanadate anion was evaluated by using valence sum calculations to derive the valence deficiency for the oxygen atoms (Ss = S(r/ 1.791) À5.1 , r is the VÀOd istance, s is the bond number). [18] The calculated Ss values for all oxygen atoms in [V 10 O 28 ] 6À were close to 2.0 (1.69-2.04 for 1 and 1.67-2.05 for 2;T ables S2 and S5 in the Supporting Information), which indicated that there were no protonated sites. The Ss values werea lso calculated for the vanadium atoms (Ss = Sexp[(1.803Àr)/0.37]), [19] which confirmed that the vanadiumo xidation state was + 5( Tables S1 and S4 in the Supporting Information).…”
Section: X-ray Crystallographymentioning
confidence: 72%
“…Nevertheless, the compounds that consist of V 10 O 28 clusters linked to TMCs or organic cations have been rarely reported up to now [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]…”
Section: Introductionmentioning
confidence: 99%